Óleo de citronela no controle de ectoparasitas de bovinos - Agnolin, Carlos Alberto (2009)
This research was aimed to evaluate in vivo effects of citronella oil on cattle ectoparasites. Two experiments with different levels of citronella oil (I) and the relationships with phytotherapic and the synthetic acaricide (II) were evaluated. In experiment I, twenty Holstein cows were allocated in four groups of five animals. The treatments were: negative control, amitraz at 0.025% and citronella oil at 3 and 4%. Engorged ticks and flies (horn fly, stably fly and domestic fly) were evaluated on animals before (mean of days -3, -2, -1) and at 3; 7 and 14 days after treatment. The efficacy of control ticks was 89.2; 36.5 and 35.8% for amitraz and citronella oil at 3 end 4% respectively, on 14th day post-treatment. Lower control of flies was observed for phytotherapic treatments. In experiment II, fifteen Holstein cows were allocated in three groups of five animals. The treatments were: negative control, amitraz at 0.025% and citronella oil at 4%. Engorged ticks and flies were evaluated on animals before (mean of days -3, -2, -1) and at 7; 14; 21 and 28 days after treatment. In 28 days there was need to reapply the amitraz to control engorged ticks. The relationship among the number of application was the 1:2.5 for amitraz and citronella oil, respectively. The efficacy in control ticks were 71.8 and 30.9% for amitraz and citronella oil at 4% respectively. Lower control of flies was observed for phytotherapic treatment.